A Highly Selective Fluorescence Turn‐On Probe for the Sensing and Bioimaging of Hypochlorite Anion in Aqueous Media. Issue 23 (20th June 2018) - Lohar, Somenath; Patra, Ayan; Roy, Priya; Babu, Santi P. Sinha; Chattopadhyay, Pabitra
Abstract: A newly designed and structurally characterized 2, 6‐diformyl −4‐methyl‐phenol based moiety detects the hypochlorite ions as low as 75.9 nM selectively in DMSO–H2 O (1:9, v/v) solution (100 mM HEPES buffer, pH 7.4) based on oxidation cleavage reaction of the thioacetal linkage. To establish this reaction based pathway in favor of sensing hypochlorite ions, the detailed spectroscopic studies have been carried out systematically supported by theoretical (DFT) studies. The efficacy of this non‐cytotoxic probe has been checked by acquiring the fluorescence images of the distribution of the hypochlorite (ClO − ) ion in living cells. Abstract : A newly synthesized and structurally characterized 2, 6‐diformyl −4‐methyl‐phenol based moiety detects selectively the hypochlorite ions as low as 75.9 nM selectively in DMSO–H2 O (1:9, v/v) solution based on oxidation cleavage reaction of the thioacetal linkage. This reaction based pathway for sensing hypochlorite ions have establish by detailed spectroscopic and theoretical (DFT) studies. This non‐cytotoxic probe is also useful to detect the distributions of the ClO − anion in living cells at biological pH.